2011
DOI: 10.1021/om200683q
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Ligand Reactivity in Tantalum(V) Compounds: Experimental and Computational Evidence for Allyl Transfer to the Formamidinate Ligand in fac-Ta(NMe2)31-allyl)[iPrNC(H)NiPr] via a Metallo-Claisen Rearrangement

Abstract: The first alkyl-amido tantalum(V) compounds having the composition Ta(NMe 2 ) 4 R (where R = Et, i Pr, t Bu, CH 2 SiMe 3 ) were reported by Chisholm et al. in 1982. 1 These monoalkyl derivatives were prepared from TaCl(NMe 2 ) 4 and the appropriate organolithium reagent. The molecular structure of the t Bu derivative revealed a square-pyramidal tantalum compound, and the alkyl group was situated at the apical site. More recently, Xue and co-workers have prepared the related silyl-substituted Ta-(NMe 2 ) 4 R d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Calculations (meta-GGA) TPSS and B3LYP methods revealed that allyl group transfer from tantalum in the fac-Ta(NMe 2 ) 3 (Z 1 -allyl)[ i PrNC(H)N i Pr] Ta(NMe 2 ) 3 -[ i PrNCH(allyl)N i Pr] rearrangement occurs via a [3,3]-sigmatropic rearrangement (Scheme 19). 34 The allyl and the Ta-N-C(formamidinate) fragments participate via a transition structure that adopts a chair-like geometry. The TPSS calculated activation barrier for the metallo-Claisen rearrangement is 5.1 kcal mol À1 lower and in better agreement with the results of NMR experiment than the barrier determined by the B3LYP calculations.…”
Section: [33] Shiftsmentioning
confidence: 99%
“…Calculations (meta-GGA) TPSS and B3LYP methods revealed that allyl group transfer from tantalum in the fac-Ta(NMe 2 ) 3 (Z 1 -allyl)[ i PrNC(H)N i Pr] Ta(NMe 2 ) 3 -[ i PrNCH(allyl)N i Pr] rearrangement occurs via a [3,3]-sigmatropic rearrangement (Scheme 19). 34 The allyl and the Ta-N-C(formamidinate) fragments participate via a transition structure that adopts a chair-like geometry. The TPSS calculated activation barrier for the metallo-Claisen rearrangement is 5.1 kcal mol À1 lower and in better agreement with the results of NMR experiment than the barrier determined by the B3LYP calculations.…”
Section: [33] Shiftsmentioning
confidence: 99%
“…The former complex reacts with i PrNC(H)NH i Pr to give the five coordinate [Ta(NMe 2 ) 3 { i PrNCH-(allyl)N i Pr}] via a potential metallo-Claisen rearrangement. 52 The reactions between the tantalum dimethyl and diphenyl complexes, [(ONO cat )TaR 2 ] (R = Me, Ph; ONO cat = N,N-bis(3,5-t Bu 2 -2-phenoxide)amide) and aryl azides and 1,2-diphenylhydrazine, were reported. 53 55 The mechanism for the reaction of H 2 with ''end-on-bridged'' dinitrogen bimetallic complex of [Cp*Ta(MeC(N i Pr) 2 ] was examined by DFT studies.…”
Section: Niobium and Tantalummentioning
confidence: 99%